2022
DOI: 10.1155/2022/7657995
|View full text |Cite
|
Sign up to set email alerts
|

miR-590-5p Overexpression Alleviates β-Amyloid-Induced Neuron Damage via Targeting Pellino-1

Abstract: Alzheimer’s disease (AD) is one common degenerative disorder. However, the effects of miR-590-5p on AD and the mechanism on modulation of AD development were unclear. In this study, the miR-590-5p level in AD patients at mild, moderate, and severe stage as well as APP/PS1 transgenic mice was detected by qRT-PCR. The relationship of miR-590-5p and pellino-1 (PELI1) was identified by double luciferase reporter gene assay. Afterwards, both BV-2 and HT22 cells were exposed to β-amyloid (Aβ) peptides to mimic AD ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…According to the findings, the anti-apoptotic effect of miRNA might partly be due to the inhibition of Pellino-1 (PELI1), which increased TRAF3 but decreased the expression as well as the phosphorylation of p38 MAPK and ERK1/2. Consistently, activation of the p38 MAPK pathway has been previously found in the brain tissue of AD cases [184].…”
Section: Mirnas Via the Mapk Signaling Pathway Regulate Microglia-med...supporting
confidence: 83%
See 1 more Smart Citation
“…According to the findings, the anti-apoptotic effect of miRNA might partly be due to the inhibition of Pellino-1 (PELI1), which increased TRAF3 but decreased the expression as well as the phosphorylation of p38 MAPK and ERK1/2. Consistently, activation of the p38 MAPK pathway has been previously found in the brain tissue of AD cases [184].…”
Section: Mirnas Via the Mapk Signaling Pathway Regulate Microglia-med...supporting
confidence: 83%
“…Using both BV-2 and HT22 cells stimulated with Aβ as an in vitro AD model, Shang et al [184] found that miR-590-5p mimic injection restored cell viability by improving proliferation. In addition, miR-590-5p levels were found to be reduced in the serum of both AD patients and APP/PS1 transgenic mice.…”
Section: Mirnas Via the Mapk Signaling Pathway Regulate Microglia-med...mentioning
confidence: 99%
“…In addition, the E3 ligase Pellino, expressed in a variety of nerve cells, is a key regulator of microglia-mediated autoimmune neuroinflammation, and it is engaged in the ubiquitination and degradation process of c/EBPβ. The depletion of Pelil can increase the expression of c/EBPβ and CD36, thereby promoting the phagocytic activity of microglia to further improve the clearance of Aβ [ 135 , 136 ]. Pleckstrin homology-like domain family A member 1 (PHLDA1) is an important modulator of microglia-mediated inflammation.…”
Section: Epigenetic Regulation In Inflammationmentioning
confidence: 99%
“…MiR‐485‐3p‐CD36 axis weakened the phagocytosis of Aβ in vitro and in vivo and might promote cell apoptosis in AD 138 . Table S3 summarizes all the abnormally expressed and cell apoptosis‐related miRNAs in AD patients 132–160 . These miRNAs can form ‘miRNA‐mRNA’ axis in regulating cell apoptosis in AD.…”
Section: Abnormally Expressed Ncrnas In Ad Patients In Regulating Cel...mentioning
confidence: 99%
“… 138 Table S3 summarizes all the abnormally expressed and cell apoptosis‐related miRNAs in AD patients. 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 These miRNAs can form ‘miRNA‐mRNA’ axis in regulating cell apoptosis in AD.…”
Section: Abnormally Expressed Ncrnas In Ad Patients In Regulating Cel...mentioning
confidence: 99%